Pengembangan Karakter Ikari Shinji Dalam Anime Neo Genesis Evangeliom - Sutanto, Marisa Rianti; Wahyudi, Adriel Hans (Jurnal Sakura : Sastra, Bahasa, Kebudayaan dan Pranata Jepang, 2021)
This research discusses the character development of the main character Ikari Shinji from the anime Neon Genesis Evangelion. Neon Genesis Evangelion is an anime series directed by Hideaki Anno that tells the story of humanity's struggle against shitos using a giant robot called Evangelion. To interpret the character of the main character, the method used is descriptive analysis, and the analysis refers to Weiland's theory of character development. The results of the research show that Ikari Shinji at the beginning of the story has a ‘lie’ that he believes in, namely running away from problems. However, he has the capability to beat ‘the lie’. Throughout the story he gets the consequences of his ‘lie’, he also finds out the truth and what he actually needs. At one point he had to make a decision between the truth and the ‘lie’. The result was Ikari Shinji's old self becomes 'dead' after he made that decision. He left the ‘lie’ and proved that he had developed into a better person. The story’s ending is the answer to this anime thematic question.